Updated insight into the characterization of nano-emulsions. (2nd January 2023) - Wang, Xinyue; Anton, Halina; Vandamme, Thierry; Anton, Nicolas
ABSTRACT: Introduction: In most of the studies, nano-emulsion characterization is limited to their size distribution and zeta potential. In this review, we present an updated insight of the characterization methods of nano-emulsions, including new or unconventional experimental approaches to explore in depth the nano-emulsion properties. Area covered: We propose an overview of all the main techniques used to characterize nano-emulsions, including the most classical ones, up to in vitro, ex vivo and in vivo evaluation. Innovative approaches are then presented in the second part of the review that presents innovative, experimental techniques less known in the field of nano-emulsion such as the nanoparticle tracking analysis, small-angle X-ray scattering, Raman spectroscopy, and nuclear magnetic resonance. Finally, in the last part we discuss the use of lipophilic fluorescent probes and imaging techniques as an emerging tool to understand the nano-emulsion droplet stability, surface decoration, release mechanisms, and in vivo fate . Expert opinion: This review is mostly intended for a broad readership and provides key tools regarding the choice of the approach to characterize nano-emulsions. Innovative and uncommon methods will be precious to disclose the information potentially reachable behind a formulation of nano-emulsions, not always known in first intention and with conventional methods.